REDISCOVERING THE TOURIST PATRONAGE OF TANDANG SORA SHRINE: STRENGTHENING THE HISTORICAL TOURISM INDUSTRY (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study examines the key factors influencing the renewed interest and ongoing support for the Tandang Sora Shrine in Quezon City. Emphasis is placed on its cultural and historical significance, the profile of its visitors, available infrastructure, and online visibility. Despite its importance as a heritage site, the shrine continues to face challenges such as poor sanitation, the absence of souvenir shops, limited seating, safety issues, and inadequate amenities, all of which negatively impact the overall visitor experience. This research adopts a descriptive design to gather comprehensive data on the Tandang Sora Shrine, aiming to accurately portray visitor experiences and site conditions without determining cause-and-effect relationships. Data were collected through surveys, case studies, and direct observations. A total of 50 visitors participated in the survey, selected through simple random sampling using Cochran’s (1977) formula to ensure representativeness. The study emphasizes the importance of addressing existing issues to improve visitor experience and deepen public appreciation of the shrine’s historical significance. Key recommendations include improving infrastructure, enhancing safety and security, creating a dedicated souvenir shop, and expanding the shrine’s digital reach through social media engagement and virtual tour offerings. These initiatives aim to bridge the gap between heritage conservation and contemporary visitor expectations, ensuring the site’s long-term viability and establishing it as a benchmark for managing other historical landmarks in the city.
Keywords: tandang sora shrine; cultural heritage; visitor experience; infrastructure improvement; digital presence; historical preservation; tourism development; quezon city; descriptive research; sustainability